ANALISIS SISTEM INFORMASI AKUNTANSI PENGGAJIAN DALAM MENUNJANG EFEKTIFITAS PEMBAYARAN GAJI PADA PT SINDO UTAMA JAYA - Ferdila Ferdila; Siti Nur Lailiyah (Jurnal Kajian Akuntansi dan Auditing, 2022)
This study discusses payroll accounting information systems, salary calculations and accounting treatment for salary payments at PT. Sindo Utama Jaya. The research was conducted in the Finance and Personnel department at PT. Sindo Utama Jaya. The research method is descriptive qualitative while the data used are qualitative and quantitative data. Sources of data come from primary and secondary data. The payroll accounting system at PT Sindo Utama Jaya is divided into various interrelated processes and procedures. The procedures that make up the payroll accounting system are procedures for recording employee personal data, recording attendance, recording employee overtime time, calculating employee salaries, making salary reports procedures, procedures for making cash out evidence and salary payment procedures. The documents used in the process of the company's payroll system are complete enough according to the theory according to experts, but are not implemented optimally. The salary standards of employees at PT Sindo Utama Jaya have followed the City Minimum Wage standards set by the government. The calculation of attendance hours and employee overtime hours, as well as making payroll reports are still done using a computer with Microsoft Office excel without a payroll application which allows for errors and mistakes in salary calculations. Salary payment system at PT. Sindo Utama Jaya is carried out in two ways, namely transfers to employee accounts and cash payments.